Schwere Hämophilie A: Wann werden Kinder diagnostiziert, wann beginnen sie zu bluten? - Pollmann, H.; Siegmund, B.; Richter, H. (Hämostaseologie, 2010)
Based on a previous investigation, the aim of this study was to re-evaluate when children with severe haemophilia A (FVIII : C <1%) are diagnosed and when they start to bleed. Data from previously untreated patients (n = 20) were collected. Results: 95% of the patients experienced their first bleeding episode at the age of less than one year. On average, the first non-joint bleed occurred at the age of 0.85 years, whereas the first joint bleed developed approximately a half year later at the age of 1.49 years. Compared to the previous investigation children were diagnosed earlier, i.e. at the age of 3.7 month on average.
Keywords: Haemophilia A; factor VIII; age at diagnosis